Quercetin attenuates myocardial ischemia-reperfusion injury via downregulation of the HMGB1-TLR4-NF-κB signaling pathway - Dong, Li-Ya (Am J Transl Res, 2018)
The goal of this study was to assess the ability of quercetin (Qu) to protect against myocardial ischemia-reperfusion injury. Cardiac injury was assessed in the context of global ischemia of isolated hearts, coronary artery ligated rats, and H9C2 cells. Qu was shown to significantly inhibit inflammatory cytokine production in coronary artery occlusion-induced rats, isolated hearts, and H9C2 cells. Electrocardiographic analysis revealed a restoration of the ST segment to normal levels following treatment of Qu. Triphenyltetrazolium chloride (TTC) staining and pathological analysis showed that Qu could significantly alleviate myocardial injury in vivo. Furthermore, ex vivo analyses showed improved recovery of heart function in response to Qu, characterized by enhanced myocardial contractility and coronary flow in isolated hearts. From a mechanistic standpoint, these effects appeared to be mediated through the HMGB1-related pathway, with expression of downstream targets significantly downregulated in rats, isolated hearts, and H9C2 cells following Qu treatment. Taken together, these data demonstrate the protective effects of Qu against myocardial injury via inhibition of the HMGB1 pathway in a myocardial ischemia-reperfusion injury (I/R) model.